International perspectives on public administration - Sardaryan, Henry T. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"International Perspectives on Public Administration uses civilizational theory for grouping and analyzing systems of public administration in different countries around the world, thus offering a global perspective which reveals how different systems may be divided by cultural borders of the modern day. The author uses different scientific disciplines, namely political theory, political philosophy, law and economics, to offer comparative analysis of the genesis and development of public administration systems in the Western, Orthodox, Islamic, Confucian, Hindu, Buddhist, Japanese and African civilizations, together with reviewing their experience in application of the most modern and progressive practices of public management. This book will be of great interest to students and scholars of public administration, political science, public management, public policy, and civilizational theory"--
OCLC-licensed vendor bibliographic record.
Keywords: Public administration -- Philosophy; Comparative government; POLITICAL SCIENCE / General